The Long Arc of Justice: Forging a Convention for Crimes Against Humanity - Leila Nadya Sadat (Washington University Global Studies Law Review, 2025)
This Article presents a comprehensive overview of the development, challenges, and future prospects of creating and negotiating a global treaty for crimes against humanity. It honors pioneers in the field and acknowledges the contributions of various individuals and entities to the Crimes Against Humanity Initiative, which the author established in 2007. It traces the historical context of atrocities such as slavery and the slave trade, linking them to the modern concept of crimes against humanity. The Article reviews the evolution of international criminal law, particularly under the Rome Statute of the International Criminal Court (ICC), emphasizing the need for a new treaty to fill gaps left by existingf rameworks. Highlighting contemporary examples like the Syrian Civil War, it underscores the preventive power of prosecuting crimes against humanity, as a move towards preventing the commission of atrocity cascades, before they descend into armed conflict and genocide. The Article describes the multi-decade effort to draft and promote a new treaty, including significant milestones, such as the adoption of the International Law Commission’s (ILC) 2019 Draft Articles, and the protracted and ultimately successful advocacy within the U.N. General Assembly’s Sixth (Legal) Committee to achieve a consensus resolution in 2022 that allowed the process to move forward. The 2024 adoption of GA Resolution 79/122, which authorizes convening a United Nations Diplomatic Conference for crafting a comprehensive legal instrument, was a critical achievement, setting the stage for negotiations over the next several years. The Article reflects upon the enduring struggle for justice and the imperative to adopt, ratify, and enforce a new treaty, drawing historical parallels with the abolition of the transatlantic slave trade. It concludes with a call for continued dedication to ending impunity for crimes against humanity globally.
Keywords: Crimes Against Humanity; Global treaty; ICC; Rome Statute; ILC; 2019 Draft Articles; GA Resolution 79/122